Bombyx mori Pupae Efficiently Produce Recombinant AAV2/HBoV1 Vectors with a Bombyx mori Nuclear Polyhedrosis Virus Expression System - Qian Yu; Pengfei Chang; Xiaoxuan Liu; Peng Lü; Qi Tang; Zhongjian Guo; Jianming Qiu; Keping Chen; Qin Yao (Viruses, 2021)
Recombinant adeno-associated virus (AAV) vectors have broad application prospects in the field of gene therapy. The establishment of low-cost and large-scale manufacturing is now the general agenda for industry. The baculovirus-insect cell/larva expression system has great potential for these applications due to its scalability and predictable biosafety. To establish a more efficient production system, Bombyx mori pupae were used as a new platform and infected with recombinant Bombyx mori nuclear polyhedrosis virus (BmNPV). The production of a chimeric recombinant adeno-associated virus (rAAV) serotype 2/human bocavirus type-1 (HBoV1) vector was used to evaluate the efficiency of this new baculovirus expression vector (BEV)–insect expression system. For this purpose, we constructed two recombinant BmNPVs, which were named rBmNPV/AAV2Rep-HBoV1Cap and rBmNPV/AAV2ITR-eGFP. The yields of rAAV2/HBoV1 derived from the rBmNPV/AAV2Rep-HBoV1Cap and rBmNPV/AAV2ITR-eGFP co-infected BmN cells exceeded 2 × 104 vector genomes (VG) per cell. The rBmNPV/AAV2Rep-HBoV1Cap and rBmNPV/AAV2ITR-eGFP can express stably for at least five passages. Significantly, rAAV2/HBoV1 could be efficiently generated from BmNPV-infected silkworm larvae and pupae at average yields of 2.52 × 1012 VG/larva and 4.6 × 1012 VG/pupa, respectively. However, the vectors produced from the larvae and pupae had a high percentage of empty particles, which suggests that further optimization is required for this platform in the future. Our work shows that silkworm pupae, as an efficient bioreactor, have great potential for application in the production of gene therapy vectors.